Владимир Высоцкий: [сборник] / В. С. Высоцкий - Высоцкий Владимир Семенович (Антология Сатиры и Юмора России XX века, 2003)
Экземпляры: Ф-4 (20221206) / Инвентарный номер: 98116 / Цена: / Сис.шифр: 84(2=411.2)6-5 / Авт.знак: В 93 / ББК: 84(2=411.2)6-5